Isoteritinoin induced transient myopia and acute secondary closed angle glaucoma in a healthy individual - Abdallah E. Hammour (Al-Azhar Assiut Medical Journal)
Isotretinoin infrequently reported to be associated with the development and deterioration of myopia. Here we present a 37-year-old-woman on oral-isotretinoin-(20 mg/d)-for-acne-treatment presented with bilateral blurred vision and ocular pain for one week. Her UCVA was 20/200OD and 20/300OS. The refraction was−4.50Dâ 1.0D×180OD and−5.5Dâ 0.5D×30°OS. IOP was 68-mmHg. Slit-lamp examination revealed mild corneal edema, mid-dilated sluggish reaction pupils, and markedly shallow AC without inflammation. Gonioscopy-showed shallow AC with 360° appositional angle closure. Isotretinoin was discontinued, and anti-glaucoma and cycloplegic were started. A few days later all ocular manifestations were resolved. We think that an adverse reaction to oral isotretinoin may result in bilateral temporary myopia shift and acute secondary closed angle glaucoma.